Proposta de Planejamento de Ensino e Avaliação do Rendimento Escolar - Pecher, Fristz Cristof Rudolf; Rodrigues, José Luiz Pieroni; Santos, Silas Martins dos; Moreira, Paulo; Bagnareli, Moacyr; Brito, Maria do Socorro Taurino; Depresbiteris, Léa; Pinto, Alaor Correa (Educação e Seleção, 2013)